Чудеса света. Новый мир - Калашников Виктор Иванович (Энциклопедия тайн и загадок, 2009)
Экземпляры: ф.14 (2010) / Инвентарный номер: 53441 / Цена: / Сис.шифр: 26.89(0) / Авт.знак: К 17 / ГРНТИ: 39.15 / ББК: 26.89(0)